Follicular dynamics of the natural estrous cycle in buffalo (Bubalus bubalis) - Sanchez valencia, Jorge Alberto (2019)
The aim of the study was to monitor the follicular dynamics of the natural estrous cycle in the domestic buffalo in Colombia. Patterns of growth and regression of ovarian follicles in two consecutive oestrus cycles in 11 buffalos were evaluated. Ultrasound examination of the ovaries were conducted every second day to establish patterns of follicular waves, number of waves, emergency day, number of follicles recruited, and characteristics of the dominant follicle (DF) and of the corpus luteum (CL). Progesterone (P4) concentration was determined by radioimmunoassay. Seventeen normal cycles (2, 11 and 4 estrous cycles with one, two and three follicular waves, respectively) were evaluated. The inter ovulatory interval was 12.5 ± 2.7, 20.5 ± 1.2 and 28.8 ± 1.9 days for cycles with 1, 2 and 3 follicular waves, respectively. Follicular waves emerged on days 0 ± 2.3 for cycles with 1 wave, on days 2.3 ± 1.0 and 10.5 ± 1.0 in cycles with two waves and on days 1.6 ± 1.25, 8.0 ± 1.9 and 20.8 ± 1.6 (mean ± e.e.) in cycles with the waves. The concentration of P4 on the day of maximum diameter of CL on average was 7.2 ± 6.6 ng/ml. In conclusion, follicular dynamics of the Colombian buffalo is characterized by patterns of one, two and three follicular waves, with predominance of two-wave cycles.